Analysis of strategies applied based on the results obtained in the diagnostic tests in the English teaching-learning process of students at Décimo año “A” at Escuela de Educación Básica 21 de Abril in Riobamba city, Chimborazo province in the academic period April 2021 – September 2021 - Quiguiri Quispe, Jennyfer Lissette (2023)
Nowadays, English language is considered a fundamental pillar of the educative process. In Education, assessment is contemplated as a dynamic process between teachers and students to fulfill a significant role in the class. According to this information, the diagnostic test is vital in the participant´s teaching-learning process. The use of this kind of test in the classroom is helpful to allow recognizing the student´s strengths and weaknesses. Through different activities can collect essential information and improve their language skills. The teacher can interpret the data to determine their future performance. In this context, it was proposed the following study entitled “Analysis of strategies applied based on the results obtained in the Diagnostic tests in the English teaching-learning process of students at Décimo año “A” at Escuela de Educación Básica 21 de Abril in Riobamba city, Chimborazo province in the academic period April 2021 – September 2021”. This research aimed to analyze the strategies applied based on the results obtained in the diagnostic tests in the English teaching-learning process. Besides, in this investigation, a qualitative paradigm and exploratory research were used. Also, the researcher adopted the triangulation method for the analysis and interpretation of these results. Based on this previous information, an interview and observation were applied with the appropriate instruments as a semi-structured interview and observation guide with the English teacher and the students in the institution beforementioned. The results of this research were focused on the importance of the Diagnostic test inside the classroom. Therefore, it shows the ability to apply specific techniques as feedback to improve students´ English teaching-learning process.